(untitled) (Bangladesh Journal of Pharmacology, 2016)
The present study is aimed to investigate the phytochemical screening and biological activities of methanolic extract of Cyperus scariosus roots. Dried plant was grounded and extracted with methanol to prepare methanol crud extract. In vitro biological tests were conducted using this methanolic extracts according to the standard procedure. 100% death rate of brine shrimp was perceived at 3 mg/mL of plant extract after 72 hours. The extract showed action against Aspergillus flavius i.e. 90% followed by A. niger (91%) while the highest activity was shown against A. fumegatrus (94%). Important scavenging results were detected during scavenging of free radicals viz; 92.2% against DPPH, 82.2% to ABTS, 75.8% to hydrogen peroxide, 88.1% to ?-carotene, 86.1% to hydroxyl radical and 89.4% against phosphomolybdate at 3 mg/mL were obtained. The results obtained in this study point out that extract showed significant biological activities which might be due to the presence of bioactive constituents.